Peningkatan Keterampilan Pertanian Generasi Muda melalui Pelatihan Budidaya Hortikultura Sayuran di SMP Negeri 1 Sumbang, Banyumas: Empowering the Younger Generation Through Vegetable Horticulture Training at SMP Negeri 1 Sumbang, Banyumas - Primayuri, Deviana; Purba, Dumaris Priskila; Sundari, Dini; Sevirasari, Nindy; Hidayati, Wilujeng; Az Zahroh, Zulfa (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The agricultural sector's future in Indonesia heavily depends on the role of the younger generation. They have the potential to drive agriculture toward progress and sustainability. One group that plays an important role in Junior High School (SMP) students, particularly at SMPN 1 Sumbang in Banyumas Regency. This activity aims to enhance the skills and knowledge of students at SMP Negeri 1 Sumbang in horticultural crop cultivation, especially vegetables, as a strategic step to foster young people's interest in agriculture. The SMP Negeri 1 Sumbang community service activity was held on December 12, 2024. This program targeted 30 ninth-grade students and included counselling sessions, hands-on practice with teachers and students, and activity evaluations—an initial evaluation before counselling and a final evaluation afterwards. The evaluation results indicated an increase in students' understanding of vegetable cultivation techniques, with the initial understanding level rising from 33% to 85% after the final evaluation. This improvement demonstrates the success of the community service program in enhancing students' knowledge and skills in vegetable farming. However, this agricultural practice must be carried out continuously so that students' skills can keep developing.